The Russian Protest Movement of 2011–2012: A New Middle-Class Populism - Magun, Artemy (Stasis, 2014)
The article deals with the mass civic protests that shook Russia in 2011–2012. The article examines the question of populist and ideological self-determination on the part of the protesters qua political subjects. Based on a group empirical study of protest rally participants, the author points to the frequent populist self- identification used by the protesters. They called themselves “the people,” although they obviously represent a minority, and share some special features such as a relatively high level of education and income. The article analyzes this phenomenon within the context of the theory of populism. It reconsiders some aspects of this theory and identifies the Russian case as a historically new but currently quite typical version of populism.